THE EFFICACY OF PIE (POINT, ILLUSTRATION, EXPLANATION) STRATEGY IN TEACHING WRITING NARRATIVE TEXT - Tsuraya, Annisa Shofa; Nur, Nur Aliyah (English Language, Linguistics, and Culture International Journal, 2021)
This research aimed at finding out the students writing ability in term of narrative text through using PIE (point, illustration, explanation) strategy. Pre-experimental method was applied in this research. The research had conducted with treatment, where the class consisted of four meetings. The location of this research was done at the second grade students of one of state junior high schools with 20 students and stand by one class using pre-test and post-test design. The instrument was used written test as pre-test and post-test. In pre-test the students made the material about narrative text that they had read or listened without involving PIE (point, illustration, explanation) strategy. While in the post-test students also made the material about narrative text that they had read or listened which was involved PIE (point, illustration, explanation) strategy. The findings indicated that the application of PIE (point, illustration, explanation) strategy was significant to improve the students’ writing ability and it was proved by means score in pre-test was 51.75 and the post-test was 75.25. it means that the means score of post-test is greater then the pre-test, and also there was significant because the result of t-test was 6.94 and t-table was 2.093. It means that was significant because t-table was smaller than t-test. Thus, can be concluded that the use of PIE (Point, Illustration, Explanation) Strategy improved the students’ writing achievement.